2000
DOI: 10.1080/00288330.2000.9516921
|View full text |Cite
|
Sign up to set email alerts
|

Induced spawning and early ontogeny of New Zealand freshwater eels{Anguilla dieffenbachiiandA. australis)

Abstract: Knowledge on the reproductive biology of New Zealand freshwater eels (Anguilla australis Richardson and A. dieffenbachii Gray) is limited to changes associated with gametogenesis in the adults; details pertaining to embryonic and larval development are not available, but are of obvious benefit for a better understanding of the eel life history and for artificial propagation programmes, whether for aquaculture or conservation purposes. Therefore, eels were artificially matured and eggs fertilised with sperm fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 25 publications
1
52
0
Order By: Relevance
“…Since then, such experimental procedures have been used extensively, mainly with the purpose of obtaining viable larvae for aquaculture development of eels. Studies have focused solely on the establishment of successful protocols: dose and rhythm of hormone injections, timing and type of ovulation primers, optimal water temperature, salinity, and optimal body indices to predict ovulation (Sorensen & Winn 1984, Prokhorchik 1986, Dufour et al 1988, Ohta et al 1997, Kagawa et al 1998, Lokman & Young 2000, Pedersen 2004, Palstra et al 2005. Ovulated eggs and larvae were successfully obtained in a number of studies; however the proportion of ovulating females remained very low, as well as the fertility and hatchability of the eggs (Kagawa 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, such experimental procedures have been used extensively, mainly with the purpose of obtaining viable larvae for aquaculture development of eels. Studies have focused solely on the establishment of successful protocols: dose and rhythm of hormone injections, timing and type of ovulation primers, optimal water temperature, salinity, and optimal body indices to predict ovulation (Sorensen & Winn 1984, Prokhorchik 1986, Dufour et al 1988, Ohta et al 1997, Kagawa et al 1998, Lokman & Young 2000, Pedersen 2004, Palstra et al 2005. Ovulated eggs and larvae were successfully obtained in a number of studies; however the proportion of ovulating females remained very low, as well as the fertility and hatchability of the eggs (Kagawa 2003).…”
Section: Introductionmentioning
confidence: 99%
“…(Ellerby et al 2001b;Sasai et al 2001;Tseng et al 2003;Dannewitz et al 2005), since these fish species have a few morphological forms, inhabit a different environment depending on their life stage or age (Poole & Reynolds 1998;Tzeng et al 1999;Tsukamoto & Arai 2001;Powles & Warlen 2002) and migrate over long distances (Virbickas 2000;Katoh & Kobayashi 2001;Okamura et al 2002;Limburg et al 2003;Bardonnet & Riera 2005) to their spawning grounds. No one knows exactly where the European eels (Anguilla anguilla) spawning ground is (Lokman & Young 2000;Ringuet et al 2002). The smallest larvae found in the Sargasso Sea, south of Bermuda, suggest that spawning of the A. anguilla as well as that of the American eel (Anguilla rostrata) occurs nearby (Wirth & Bernatchez 2001Mank & Avise 2003;Versonnen et al 2004;Dannewitz et al 2005;Palstra et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, fish (carp or salmon) pituitary extract and hCG are currently used to obtain maturation in Anguilla spp in both sexes, with better results in males than in females (Ohta et al, 1997;Lokman and Young, 2000;Asturiano et al, 2002Asturiano et al, , 2005Palstra et al, 2005;Pérez et al, 2008;Peñaranda et al, 2010). Recently, in males, it was demonstrated that stimulation by recombinant hCG produces better results in term of sperm production than traditional treatment with purified hCG (Gallego et al, 2012).…”
Section: Indexmentioning
confidence: 99%
“…While in male eels good quality sperm is obtained (Ohta et al, 1997;Lokman and Young, 2000;Asturiano et al, 2002Asturiano et al, , 2005Palstra et al, 2005;Peñaranda et al, 2010), the quality of the eggs and, as consequence, of the embryos, is often very low (Ohta et al, 1996;Lokman and Young, 2000;Pedersen, 2003).…”
Section: Indexmentioning
confidence: 99%
See 1 more Smart Citation